METODE PREDIKSI BERBASIS GREY MODEL UNTUK PROGNOSIS PERAMBATAN RETAK - Rivco Mamoto; Stenly Tangkuman; Michael E Rembet (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2017)
The crack is one of the frequent problems in engineering field. It effectively cause the component become fail. Therefore predicting crack growth is very important. Prediction was applied, so crack can be prognosed. In order to prevent failure in a component, crack prognostics have applied. The aim of this research is developing of Grey Model as a predictor, and application of developed Grey Model on crack growth prediction. The crack growth data acquired from experimental files were employed for evaluating the proposed method. A modification has made to improve the accuracy of prediction. In addition, error parameter has involved for evaluating the predicting performance.The methodology of this paper consists of five stages. That are theoretical study, simulation of basic grey model, background value modification, simulation of modified grey model, and application of modified grey model.The result shown there are decrease of error values on the prediction. The reduction of error values of three prediction data are 14,07 %, 4,01 %, and 6,93 % respectively. Thus, the development of grey model for crack growth prognostic has successfully made.Â Keyword: Crack, Prognostics, Grey Model, Prediction Method